Exploration of chemical reaction and activation energy role of Jeffery-Hamel Jeffery fluid flow in penetrable non-parallel channels with entropy optimization - Laiq Zada; Ikram Ullah; Saeed Islam; Rashid Nawaz; Assmaa Abd-Elmonem; Fayza Abdel Aziz El Seabee; Hijaz Ahmad (Results in Engineering)
Recent research has demonstrated that non-Newtonian fluids exhibit superior heat transfer capabilities compared to conventional fluids. However, current methods for enhancing heat transfer in non-Newtonian fluids have their limitations. This study aims to address these limitations by investigating the influence of chemical reactions and activation energy on heat transfer within convergent/divergent channels, as described by the Buongiorno model. The study highlights several key outcomes like Higher convergence angles lead to pronounced concentration variations and gradients, whereas divergent channels result in more uniform concentration profiles. The parameter reflecting kinetic energy dominance over thermal energy shows that increasing this parameter decreases fluid temperature due to energy conversion to kinetic form. Additionally, a higher value enhances solute dispersion and energy transfer, while entropy generation increases with higher values, indicating greater irreversibility and energy losses. These insights are crucial for optimizing channel design in non-Newtonian fluid applications, aiding in the control of concentration gradients, management of temperature variations, and overall improvement in efficiency. Numerical computations of the proposed model were performed using the BVP4c scheme.